The application of landslide potential hazard zonation mapping in the Ebbw Valley , Gwent, Wales , United Kingdom - Zulfahmi Ali Rahman (Universiti Kebangsaan Malaysia, 1999)
The application of landslide potential hazard zonation mapping in the study area is based on the successful application of this method used in the Rhondda Valley which is also facing landsliding problems. This method involves dividing of the study area into square grids 100 ´ 100 m2 representing basic mapping and analyzing unit. The contributory factors of the slope instability were considered in preparing the potential landslide hazard map and being given an appropriate rating value. In this study, three main contributing factors were used for analysis: a slope angle, superficial deposit types and groundwater potential. This study indicates that most of the landslide areas are concentrated on the valley side and are largely triggered by the presence of human activity which also has altered the groundwater condition and surficial morphology. The landslide potential (LP) values were divided into two major categories including ‘areas with little landslip potential’(0 - 110 and 110 - 210) and ‘areas with some landslip potential’ 210 - 410 and 410 - 1200). According to this analysis, the minimal LP category occupies 54% of the study area then followed by high LP (17%). Meanwhile the slight and moderate LP categories represent 14% and 15% of the study area, respectively.